2021
DOI: 10.1182/blood-2021-153626
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia in Western Kenya: A Snapshot

Abstract: Introduction: Steady advances in the treatment of acute myeloid leukemia (AML) have improved outcomes in high-resource settings, with a 5-year overall survival rate of 29% and rising in the United States. In contrast, a diagnosis of AML in many resource-limited settings automatically confers a less than 10% one-year survival rate. To better understand this significant disparity, as well as how to narrow it, it is important to gather data illustrating the current landscape of AML management in resource limited-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 9 The median age in our study was 32 years unlike the worldwide median age of 68 years at diagnosis of adult acute leukemia; up to 58.4% of our patients were age 18-35 years, which is also consistent with other studies in RLS that show that median age of adults with acute leukemia is lower than those in RRS. 10 - 12 Younger age at diagnosis could be explained in part because of the lower average life expectancy in our setting and probable selection bias where younger patients are referred to the larger national hospitals. Patients older than 60 years have been reported to have worse outcomes than younger patients regardless of cytogenetics or prognostic classification.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 9 The median age in our study was 32 years unlike the worldwide median age of 68 years at diagnosis of adult acute leukemia; up to 58.4% of our patients were age 18-35 years, which is also consistent with other studies in RLS that show that median age of adults with acute leukemia is lower than those in RRS. 10 - 12 Younger age at diagnosis could be explained in part because of the lower average life expectancy in our setting and probable selection bias where younger patients are referred to the larger national hospitals. Patients older than 60 years have been reported to have worse outcomes than younger patients regardless of cytogenetics or prognostic classification.…”
Section: Discussionmentioning
confidence: 97%
“… 34 Still, in Kenya, a larger study of 113 patients with AML whose median age was 40 years and in which no patient received standard intensive induction chemotherapy because of inadequate supportive care showed that the median overall survival after diagnosis was only 45 days. 10 Another study showed that although toxicity was acceptable with the use of a low-intensity regimen among children with ALL, more than 70% of patients had died at 2 years and disease relapse was a substantial cause of failure. 35 Patient population heterogeneity therefore remains to be considered as a contributor to the outcome of patients with acute leukemia.…”
Section: Discussionmentioning
confidence: 99%